Basilar Artery Tortuosity Is Associated With White Matter Hyperintensities by TIMP-1 - Zhang, Dao Pei; Peng, Yan Fang; Zhang, Huai Liang; Ma, Jian Gong; Zhao, Min; Yin, Suo; Wei, Tian Tian (Frontiers in Neuroscience, 2019)
Background and Purpose To test the hypothesis that the imbalance between matrix metalloproteinases (MMPs) and tissue inhibitor of metalloproteinases (TIMPs) may play a potential role in bridging vertebrobasilar dolichoectasia (VBD) with lacunar infarction (LI) and white matter hyperintensities (WMH). Methods We studied 212 patients with vertigo who underwent multimodal magnetic resonance imaging (MRI) tests for VBD, LI, and WMH identification. We investigated biomarkers of VBD with magnetic resonance angiography (MRA) via various physical characteristics of the vertebrobasilar arteries (VBAs). Similarly, LI and WMH biomarkers were extracted using T2-weighted and fluid attenuated inversion recovery (FLAIR) images. We first determined which of these neuroimaging markers were significant identifiers of VBD, LI and the different grades of WMH. We then sought to draw potential mechanistic conclusions from these MRI-derived parameters, by associating the aforementioned biomarkers with MMP and TIMP serum levels in patient blood samples using non-parametric statistical tests. Results MMP-9 serum level was significantly higher in vertigo patients with VBAs dilation and basilar artery (BA) elongation compared to those with healthy arterial size, and the ratio of MMP-9/TIMP-1 level were higher in those patients. TIMP-1 level was also markedly higher in vertigo patients with BA tortuosity than those without BA tortuosity. The bending length (BL) of the BA was positively correlated with TIMP-1. The length, BL, and tortuosity index of the BA, as well as serum levels of TIMP-1 were greater in patients with higher WMH grades compared to those with low WMH grades. The vertebral artery and BA diameters, and the levels of MMP-2, -3, -9, TIMP-2 and cathepsin L were similar in patients with different WMH grades. Conclusion In vertigo patients, we found various probably associations between MMP-9 and TIMP-1 with arterial alterations linked to both VBD and WMH that may help with the diagnosis and treatment of such diseases in the future.